Themed issue on advances in solid state chemistry and its applications. Issue 13 (16th March 2018) - Kirk, Caroline A.; Morrison, Finlay D.; Skakle, Jan; Sinclair, Derek C.; Irvine, John T. S.
Abstract : Guest Editors Caroline Kirk, Finlay Morrison, Jan Skakle, Derek Sinclair and John Irvine introduce this Journal of Materials Chemistry A themed issue on advances in solid state chemistry and its applications, in celebration of Professor Tony West's 70th birthday.